Dependence of Geometric and Spectroscopic Properties of Double-walled Boron Nitride Nanotubes on Interwall Distance - Metin Aydin (Nanomaterials and Nanotechnology, 2014)
We have used density functional theory (DFT) and time dependent (TD)-DFT to systematically investigate the dependency of the geometric and vibroelectronic properties of zigzag and armchair-type doublewalled boron nitride nanotubes ((0,m)@(0,n) and (m,m) @(n,n)-DWBNNTs) on the interwall distance (ΔR) and the number of unit cells. The results of the calculations showed that their structural stability strongly depends on the interwall distance, but not on the number of unit cells, and the (0,m) @(0,m+9/10) and (m,m) @(n,n) with n=m+5/6 are the most energetically stable structures. The predicted electronic structures for DWBNNTs with cell lengths of one unit exhibit a strong red-shift for the ΔR below ~0.4 nm and remain almost constant for the ΔR > 0.45 nm. The calculated nonresonance Raman spectra of (0,6) @(0,n)-DWBNNTs (with cell lengths of one unit and n=12-18) indicated that the radial breathing modes (RBMs) of inner (0,6) and outer (0,n) tubes are not only diameter dependent, but also exhibit a strong blue-shift for the ΔR below ~0.35 nm and rapidly approach zero with increasing ΔR reference to the position of the RBM in the spectrum of the corresponding single wall boron nitride nanotubes, (0,n)-SWBNNTs. The calculated IR spectra of the (0,6) @(0,n)-DWBNNTs did not indicate any significant dependence on the ΔR for n > 13.